Clonal Diversity and Epidemiological Characteristics of ST239-MRSA Strains - Abd El-Hamid, Marwa I.; Sewid, Alaa H.; Samir, Mohamed; Hegazy, Wael A. H.; Bahnass, Mosa M.; Mosbah, Rasha A.; Ghaith, Doaa M.; Khalifa, Eman; Ramadan, Hazem; Alshareef, Walaa A.; Alshareef, Hanan M.; Ghoneim, Mohammed M.; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen associated with severe morbidity and mortality and poses a significant threat to public health worldwide. The genetic diversity based on sequence types of MRSA strains was illustrated in previous studies; meanwhile, the diversity along with the predominant sequence type, especially in Egypt, remains unknown. The purpose of the current study was to determine the diversity of the predominant MRSA clone ST239-MRSA (n = 50) isolated from different hosts and clinical samples and to illustrate the correlation between the resistance patterns, toxin genes, and the genetic background in Port-said and El-Sharkia Governorates, Egypt. The ST239-MRSA clone was analyzed by phenotypic antibiotyping and various genotypic assays comprising SCCmec, agr, spa, coa, and coa-RFLP in addition to toxin gene profiles. Most of the analyzed strains (40/50, 80%) were multidrug resistant (MDR), belonged to SCCmec-III, agr-I, and coa genotype I, and harbored sea and pvl genes. A negative correlation between the toxin gene profiles and antimicrobial resistance was recorded. Meanwhile, the correlation between the toxin gene profiles and the genetic background was not observed in this study. Although ST239-MRSA strains belonged to a single sequence type, they exhibited a high degree of phenotypic and genotypic diversity, indicating weak clonality and adaptability. With such diversity, it is assumed that these strains may have undergone different evolutionary processes during transmission events among and/or within a single host or tissue niche.